Long-Term Treatment Outcome after Only Popliteal Lymph Node Dissection for Nodal Metastasis in Malignant Melanoma of the Heel: The Only “Interval Node” Dissection Can Be an Adequate Surgical Treatment - Kentaro Tanaka; Hiroki Mori; Mutsumi Okazaki; Aya Nishizawa; Hiroo Yokozeki (Case Reports in Oncological Medicine)
We present a patient with malignant melanoma on his heel. Wide local excision was performed, along with sentinel lymph node biopsy of the inguinal and popliteal lesions. The primary site was clear of tumor at all margins; the inguinal nodes were negative, but the popliteal node was positive for metastatic melanoma. Only radical popliteal lymph node dissection was performed. The patient went on to receive adjuvant chemoimmunotherapy. There was no recurrence or complication until the long-term followup. Popliteal drainage from below the knee is uncommon, and the rate of popliteal-positive and inguinal-negative cases is estimated to be less than 1% of all melanomas. There is no established evidence about how to treat lymph nodes in these cases. Because we considered popliteal nodes as a regional, not interval, lymph node basin, only popliteal lymph node dissection was performed, and good postoperative course was achieved. The first site of drainage is the sentinel node, and the popliteal node can be a sentinel node. The inguinal node is not a sentinel node in all lower extremity melanomas. This case illustrates the importance of individual detailed investigation of lymphatic drainage patterns from foot to inguinal and popliteal nodes.